FLOWER BUD REMOVAL AND EARTHING UP TIME INCREASED GROWTH AND TUBER YIELD OF POTATO AT EASTERN TIGRAY, ETHIOPIA - Gebregwergis Fitsum; Mehari Gebremichael; Hailay Gebremedhin (Indonesian Agency for Agricultural Research and Development, 2019)
In Ethiopia, potato is a staple food crop and source of cash income for smallholder farmers, but the national average yield in farmers’ field is lower than experimental yields due to poor agronomic activities. The study aimed to determine the effects of flower removal and earthing up time on growth and tuber yield of potato. The experiment comprised of three flower removal stage and five earthing up time treatments, which were laid out in a randomized complete block design of 3x5 factorial arrangements with three replications. Results indicated that plant height, stem number, tuber length and tuber diameter were shown significantly affected (p < 0.05) by the main effect of flower removal and earthing up time but not by their interaction. Fresh shoot biomass and physiological maturity were recorded significantly affected (p < 0.05) by earthing up time, but not by flower removal stage and its interaction with earthing up time. Total fresh biomass, marketable and unmarketable tuber yield, as well as total tuber yield were significantly affected (p < 0.05) by main factors and their interaction effects. The results clearly indicated that the highest total tuber yield (30.96 ton ha-1) was recorded from flower bud removed potato earthed up at 15 days after complete emergence. Therefore, flower bud removed potato earthed up at 15 days after full emergence was better in terms of all yield contributing characters and tuber yield.